Coping strategies among women who experienced domestic violence in Malaysia - Tengku Hassan, Tengku Nur Fadzilah (2018)
Intimate partner violence is a significant public health issues in Malaysia and evidently highlighted as a violation of women‟s human rights. It affects a large proportion of women in Malaysia. Women who have experienced intimate partner violence have consistently reported poor physical and mental health consequences. Women experiencing intimate partner violence use various strategies to cope with violent relationships. This qualitative study aims to explore the lived experiences of women‟s coping with intimate partner violence through a feminist perspective and socio-ecological framework. Additionally, the study also wanted to examine factors motivating women‟s choices of coping as well as their perception on the effectiveness of their coping strategies. Semi-structured in-depth interviews were conducted with 26 women survivors of intimate partner violence who had sought help from two women NGOs in Malaysia. The women were asked about their experiences of violence as well as their use of coping strategies and the effectiveness of the strategies. Using thematic analysis, five major themes on coping were identified; i) avoidance-denial, ii) self-strengthening, iii) resistance, iv) self-harm and v) help-seeking. Furthermore, the prominent factors to choices of coping in the data were presence of children and preserving the marriage relationship. Women felt that it is their duty to preserve the sanctity of marriage for the sake of their children. Additional factors include socio-economic status, types and severity of violence, duration of relationship/violence and availability of resources. Women reported that self-strengthening and help-seeking strategies were effectively helpful to them in addressing intimate partner violence. On the other hand, few women reported avoidance-denial and resistance strategies were only effective in certain circumstances. The findings from the study clearly show that women experiencing violence do cope with their abusive relationship in many ways according to their observation on the violent situation. Women‟s coping with intimate partner violence should be understood as a process. This study suggests the importance of intervention to women‟s readiness in response to violence. Given the fact that women always turn to informal resources for help, it is suggested that service providers work collaboratively with women NGOs to mobilize women‟s informal social network by creating more awareness campaign on intimate partner violence. Implications for future research are discussed.